Python 3 - Pocket Primer - Parker, James R (Pocket Primer, 2017)
This book is an effort to give programmers sufficient knowledge of Python 3 to be able to work on their own projects. Although it covers all of the basic concepts, the book features a chapter on PyGame, which allows a programmer to handle graphics, mouse and keyboard interaction, and play sounds and videos. The demonstration example for that chapter is a Lunar Lander game. Another feature is the chapter on communication, which makes use of one of Python's best features: a collection of modules for sending and receiving Email, communicating between computers, and working with Twitter and Web pages. Companion files that accompany this book contain all of the code examples as complete working programs. This means that there is no need to key them in, so they can be executed and perhaps modified or expanded.